Emissions and stability performance of a low-swirl burner operated on simulated biogas fuels in a boiler environment. (5th February 2018) - Colorado, Andrés; McDonell, Vincent
Highlights: The fuel flexibility capability of a low swirl injector is assessed in detail. The experimental boiler environment used features internal EGR. The low swirl injector self-adjusts to stabilize a wide range of fuels. A validated computational methodology is used to predict emissions and stability. The method's utility for estimating burner performance and design impacts is shown. Abstract: This paper addresses the experimental and numerical modeling of NOx emissions and lean blow off (LBO) stability limits of natural gas and biogas fuels reactions stabilized with a low swirl burner (LSB). The paper presents the methodology to set up a chemical reactor network (CRN) based on experimental results and computational fluid dynamics (CFD) simulations. The CRN is a simplified representation of the fluid dynamics and energy balance of the reactive gases in the boiler environment. The CRN uses a combination of perfectly stirred reactors (PSRs) and plug flow reactors (PFRs) to couple the fluid dynamics with detailed reaction kinetics. By analyzing the CFD and CRN results, it is possible to gain insight into the relationship between internal flue gas recirculation, heat losses, geometric variables and fuel composition on the emission of NOx and the stability of the reactions. In this study, three injector configurations featuring different quarl expansion strategies were considered. Two nozzles were tested experimentally, whereas the third configuration represents an additional hypothetic design used to show the capabilities of the methodology. The numerical results are in good agreement with the experimentally observed trends and show direct relation between the emission of NOx and the lean stability limits. The quarl expansion plays a key role in the interaction of the premixed reactants and recirculated gases within the boiler environment. By varying this interaction, it is possible to attain acceptable tradeoffs between NOx emissions and burner stability. In general, the results demonstrate the ability of this design methodology to efficiently estimate burner performance and evaluate design modifications to accommodate varying fuel compositions.